Dystrophic epidermolysis bullosa: a comprehensive review of therapeutic strategies and the role of skin grafting in wound management and tissue regeneration - Jessica, Sánchez Gómez; Cedillo, Lizeth Montelongo; López, Jorge Daniel Velázquez; Bonilla, Emanuel Chew; Hernández, Roberto Hernández (International Journal of Research in Medical Sciences, 2025)
Dystrophic epidermolysis bullosa (DEB) is a severe inherited disorder caused by COL7A1 mutations, leading to deficient type VII collagen (COL7), chronic wounds, and fibrosis. Skin grafting-autologous, allogeneic, or bioengineered-offers potential for wound stabilization. This review evaluates grafting efficacy, limitations, and future directions. A systematic literature analysis (PubMed, Embase, Cochrane) highlighted clinical trials and mechanistic studies. Autologous grafts reduce wound burden but face donor-site fragility; allogeneic grafts provide temporary coverage but risk rejection. Bioengineered substitutes (e.g., gene-corrected autografts) show promise for COL7A1 restoration. While grafting remains palliative, gene-edited (e.g., CRISPR-Cas9) and tissue-engineered approaches may transform DEB care, necessitating multicenter trials for protocol standardization.